Metodología que permita estimar los factores críticos que puedan inducir la producción de arena por fuerzas de arrastre (2018)
In the present work, the compilation and analysis of different mathematical models is done for the selection of those that allow the construction of a methodology that aims to estimate critical factors in the production of sand due to drag forces. Additionally, this methodology was integrated into a user-friendly computational tool. Finally, graphical tools for the reading of parameters that influence the drag forces are presented, making use of real data of the Middle Magdalena Valley Basin.